Quo Vadis World Economy and Institutions at a Crossroads - Baldassarri, Mario.; Baldassarri, Mario. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
This study addresses the two major challenges facing the global economy: globalization and the European structural crisis. In addition, it takes a closer look at the impact of this on the Italian economy. The findings reflect on the issue of long term growth and suggest ways in which to create sustainable financial conditions for the future.